2002
DOI: 10.2118/02-09-01
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Work on the Behaviour of Synthetic Soils Contaminated with Light Hydrocarbon, and Subsequent Remediation Thereof

Abstract: The contamination of soil by light hydrocarbons is one of the most frequently encountered environmental problems. Leakage from underground storage tanks at refueling stations is the most common source, but others are refineries or production facilities. Research at the University of Calgary has been examining the application of proven petroleum reservoir engineering methods to address this issue. By use of horizontal boreholes, and cyclic water and gas injection, the contaminant can be recovered in situ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Parkin et al (2000) tested a ground penetrating radar approach to assess water contents below a wastewater trench and found the approach was comparable to results using time domain reflectometry. Finally, Aikman et al (2002) suggested that horizontal boreholes can be used to optimize recovery of hydrocarbon contamination from underground storage tanks.…”
mentioning
confidence: 99%
“…Parkin et al (2000) tested a ground penetrating radar approach to assess water contents below a wastewater trench and found the approach was comparable to results using time domain reflectometry. Finally, Aikman et al (2002) suggested that horizontal boreholes can be used to optimize recovery of hydrocarbon contamination from underground storage tanks.…”
mentioning
confidence: 99%